A DegU-P and DegQ-Dependent Regulatory Pathway for the K-state in Bacillus subtilis - Miras, Mathieu; Dubnau, David (Frontiers in Microbiology, 2016)
The K-state in the model bacterium Bacillus subtilis is associated with transformability (competence) as well as with growth arrest and tolerance for antibiotics. Entry into the K-state is determined by the stochastic activation of the transcription factor ComK and occurs in about ~15% of the population in domesticated strains. Although the upstream mechanisms that regulate the K-state have been intensively studied and are well understood, it has remained unexplained why undomesticated isolates of B. subtilis are poorly transformable compared to their domesticated counterparts. We show here that this is because fewer cells enter the K-state, suggesting that a regulatory pathway limiting entry to the K-state is missing in domesticated strains. We find that loss of this limitation is largely due to an inactivating point mutation in the promoter of degQ. The resulting low level of DegQ decreases the concentration of phosphorylated DegU, which leads to the de-repression of the srfA operon and ultimately to the stabilization of ComK. As a result, more cells reach the threshold concentration of ComK needed to activate the auto-regulatory loop at the comK promoter. In addition, we demonstrate that the activation of srfA transcription in undomesticated strains is transient, turning off abruptly as cells enter the stationary phase. Thus, the K-state and transformability are more transient and less frequently expressed in the undomesticated strains. This limitation is more extreme than appreciated from studies of domesticated strains. Selection has apparently limited both the frequency and the duration of the bistably expressed K-state in wild strains, likely because of the high cost of growth arrest associated with the K-state. Future modeling of K-state regulation and of the fitness advantages and costs of the K-state must take these features into account.